Impact of Technology and School-Based Nutrition Education Programs on Nutrition Knowledge and Behavior During Adolescence—A Systematic Review. Issue 1 (2nd January 2021) - Tallon, J. M.; Saavedra Dias, R.; Costa, A. M.; Leitão, J. C.; Barros, A.; Rodrigues, V.; Monteiro, M. J.; Almeida, A.; Narciso, J.; Silva, A. J.
ABSTRACT: This study aimed to summarize the evidence of the impact of school-based nutrition education programs that incorporate technology on the acquisition of nutrition-related knowledge and behavior change of adolescents. Literature searches were conducted using Cochrane Library, Pubmed, Scopus, Science Direct, and Web of Science databases. Studies published between 2000 and 2018, with adolescents aged from 12 to 18 years, fully available in English, which involved technology-based school interventions, and reported nutrition-related outcomes, were included. Thirteen studies met all the inclusion criteria. Overall, all studies presented positive effects, though these results did not persist. It is feasible to use technology-based approaches in this type of intervention programs, but it is necessary to improve the interventions so that long-lasting results are achieved.